RETRACTED: The Influence Of Transformational Leadership, Extrinsic Work Motivation And Work Discipline On Employee Performance Agricultural Extension And Human Resource Development Agency (Bppsdmp) Ministry Of Agriculture - Erika Triana; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This research is used to determine whether there is transformational leadership, work extrinsic motivation and work discipline on the performance of BPPSDMP employees of the Ministry of Agriculture. By paying attention to the level of control of human resources (HR), an agency is expected to make a major contribution in improving employee performance. This view also uses primary data. The data collection technique used was to use a questionnaire received by distributing questionnaires via google form to 104 employees at the Ministry of Agriculture's BPPSDMP. The information analysis approach used in this review is multiple linear regression evaluation, which is operated through the SPSS 23 application. Based on the results of this study, it shows that the variables of transformational leadership, work extrinsic motivation and work discipline have a significant effect on employee performance. That partially transformational leadership variables have a significant effect on employee performance. That the extrinsic work motivation variable has a dominant effect on employee performance. And the work discipline variable has a significant positive effect on the performance of BPPSDMP employees at the Ministry of Agriculture.